YANGI «ANTITERMIT» YEM-XO‘RAKLARINI TAKOMILLASHTIRISHDA YEM-XO‘RAK TARKIBIGA KIRITISH UCHUN TERMITOTSID MODDALARNI ANIQLASH. - Xashimova M.X. , Xashimova M.X.; Rustamov Q.J. , Rustamov Q.J.; G‘aniyeva Z.A, G‘aniyeva Z.A; Mirzayeva G.S. , Mirzayeva G.S.; Axmedov V.N. , Axmedov V.N.; Togayev U.R. , Togayev U.R. (Actual problems and prospects of the study of the fauna, 2024)
In order to identify termiticidal substances for inclusion in anti-termite feeds, the biological effectiveness of new chemical preparations was studied in the laboratory and it was found that the preparations have high toxic properties, and it was recommended to use these preparations in the preparation of feed.